Compliance of surgical hand scrub in operation theatre of teaching hospital, Chitwan - Paudel, Anish; Bista, Bishnu (Journal of Chitwan Medical College, 2019)
Background: Surgical hand scrub is an important practice that forms the base in the prevention and control of surgical site infection. The objective of the study was to evaluate the compliance of surgical hand scrub among surgical team in Operation Theatre of Teaching Hospital, Chitwan. Methods: Descriptive cross-sectional design was used. Data collection instrument (a checklist) was developed based on national and international standards of surgical hand scrub. Data was collected by observation of surgical team who were scrubbing in the Operation Theatre, Chitwan Medical College before proceeding to surgical procedures. Results: A compliance with the standards for surgical scrub prerequisites (70%), scrub process (81.53%), time of scrub (27%) and overall compliance (75.95%) observed. The total score of compliance with the standard was only 13%. The main issues found in the study were not correctly wore surgical cap and mask (44.9%), using of timer/wall clock before starting scrubbing (91.3%), improper follow the continue rotational action down opposing arms working to the elbow for one minute (53.6%) and repeated blotted dry of skin area once it done (30.4%) Conclusions: The results showed there was gap in the surgical hand scrub of the studied hospital and the compliance with the standard can be improved by simple surgical hand scrub intervention, periodical observation audit and feedback.